Risk Management Model from the Perspective of the Implementing ISO 9001:2015 Standard Within Financial Services Companies - Cătălina Sitnikov; Claudiu George Bocean; Dorel Berceanu; Ramona Pîrvu (Amfiteatru Economic)
In its new form, the ISO 9001:2015 standard activates and utilizes a thought pattern based on risk assessment functioning in parallel with the implementation of the system regarding quality management. Therefore, we strive to identify the risks and opportunities associated with the processes and products needed to create and implement a system of quality management based on the ISO 9001:2015 standard. This standard is defined by a strong client-based orientation, motivation and managerial involvement from the higher levels, as well as a process-based approach and a commitment towards constant improvement. By implementing the requirements of the new version of the ISO 9001:2015 standard, the organisation needs to determine all the processes necessary to the system of quality management, as well as to identify those which include activities dealing with risks and opportunities. Considering the importance and the impact of the requirements of the new version of the ISO 9001:2015 standard, starting from theoretical concepts and underscoring a set of research vectors, a model of financial risk assessment has been devised. The model is based on the correlation which can be established between the multiplicity of components relating to the components of the new standard structure, SL Annex, elements of an approach derived from risk patterns of processes and risk types which are assessed from the perspective of financial services companies.